COLLOID-CHEMICAL PROPERTIES OF SILICONE SURFACTANTS USED IN THE SYNTHESIS OF POLYSTYRENE LATEXES - I. A. Gritskova; A. A. Amelichev; O. A. Satskevich; A. V. Shkolnikov; A. A. Ezhova; G. A. Simakova; V. A. Vasnyov; N. A. Lobanova; B. A. Izmaylov (Тонкие химические технологии)
The synthesis of polymeric suspensions with a narrow particle size distribution is an urgent problem in modern science. The resulting polymeric microspheres are applicable in various fields of chemistry, pharmaceuticals, biology and medicine. In particular, they can be used as carriers of bioligands to create diagnostic test systems. This article presents the results of a study on the colloid-chemical characteristics of water-insoluble fluorinated silicone surfactants and kinetics of the polymerization process in their presence. The results were compared with data from studies on the properties of surfactants of similar structure not containing fluorine atoms in their structure. Studying these substances’ rheology enabled to determine the most suitable surfactants for adsorption forming a strong interfacial layer during the formation of polymermonomer particles during the polymerisation. The ability of fluorinated silicone surfactants to form a stable polymeric slurry was proved during heterophase polymerization of vinyl monomers. The resulting polymeric suspensions were characterized by a narrow particle size distribution and high aggregative stability during the synthesis and in storage.